Novos bacteriófagos de Staphylococcus aureus oriundos de leite bovino: isolamento, caracterização e atividade antibiofilme bacteriano - Barasuol, Bibiana Martins (2021)
Bacteriophages or phages are viruses that have the ability to infect and lyse bacteria through cell lysis. These viruses may represent a promising alternative for the treatment of bacterial infections, especially those caused by strains multiresistant to antimicrobial therapies, such as bovine mastitis by Staphylococcus aureus and in control of bacterial biofilms. Therefore, the objectives of this study were: isolating and characterizing S. aureus phages from bovine milk; test the efficiency of phages against bovine mastitis bacterial isolates; evaluating the ability of isolated phages to inhibit and remove bacterial biofilms from bovine mastitis isolates and standard bacterial strains. In the section corresponding to Chapter 1 of this thesis, a scientific article of meta-analysis is presented, carried out with the aim of investigating the efficiency of several S. aureus phages against different bacteria from bovine mastitis, confirming the high efficiency (80%) and specificity of most phages from the studies included in the meta-analysis. Subsequently, in Chapter 2, in manuscript 1, aimed to isolate phages from bovine milk. These phages were named B_UFSM1, B_UFSM3, B_UFSM4, and B_UFSM5 and, with the genomic and phenotypic characterization of two temperate S. aureus phages (B_UFSM4 and B_UFSM5) it was found that they belong to the order Caudovirales, family Siphoviridae and Biseptimavirus genus. In addition, with the analysis of plating efficiency, it was found that the phages B_UFSM4 and B_UFSM5 are able to infect their target host species e also have the ability to infect another bacterial species, as Rothiae terrae. Then, in Chapter 3, referring to manuscript 2, it was investigated whether phages and two combinations A (B_UFSM4 and B_UFSM5) and B (B_UFSM1, B_UFSM3, B_UFSM4 and B_UFSM5) had the ability to inhibit and remove bacterial biofilms of Staphylococcus spp. and Pseudomonas aeruginosa from bovine mastitis, as well as standard bacterial strains. It was possible to observe that the phages and combinations had antibiofilm activity and only the B_UFSM4 phage was not able to inhibit the formation and/or remove the biofilms of the tested bacterial isolates and standard strains. Thus, it is concluded that the isolated, characterized and analyzed phages should be further studied to verify their potential use as clinical therapeutic alternatives and in the control of S. aureus biofilms from bovine mastitis. Additionally, due to the COVID-19 pandemic, there were delays in the deadlines established for the completion of the morphological and molecular evaluation and characterization of the phages B_UFSM1 and B_UFSM3; therefore, these results could not be included in this thesis.